Why markets do not fail. Buchanan on voluntary cooperation and externalities - Alain Marciano (Duke University, Center for the History of Political Economy (CHOPE), 2010)
During the 1950s and 1960s, many economists were convinced that externalities were a cause of "market failures" – because individuals are not capable of internalizing the costs their actions impose to others – and therefore that the intervention of the state was necessary to allow an efficient allocation of resources. The paper presents the analyses of an economist, James Buchanan, who systematically tried to show that externalities should not be viewed as a problem for market efficiency. The central argument Buchanan used to defend markets was the human propensity to internalise the external effects of their actions and to pay for the goods they consume. We describe the intellectual trajectory he followed from the early 1950s – when he started to work on "spillover" – to the mid- 1960s to complete a consistent explanation of the efficiency of market mechanisms and private arrangements in presence of externalities. By adopting an historical perspective, we are able to show the remarkable consistency of Buchanan's claims about externalities, even though he developed them in a period when the views of economists on the question were changing dramatically.
Keywords: B2; B3; H0; H1; H4; 330; Buchanan; externalities; social cost; market efficiency; spontaneous order